Analyzing the Usability of University Siliwangi Website using Jakob Nielsen Method: Approach with User Satisfaction Surveys - Fajriani, Yuke Nurul; Hidayat, Eka Wahyu; Akbar, R Reza El (Deparment Information System, Siliwangi University, 2024)
The implementation of websites in universities has become crucial in providing a platform that enables quick and easy access to academic, administrative, and institutional information. University websites fall under the category of official websites, serving as platforms created and managed by organizations, companies, or official entities to provide information, services, and interaction with users. Universitas Siliwangi, one of the state universities in West Java, operates an official website at https://unsil.ac.id/. This website serves as a promotional tool and information hub accessible to students, faculty, staff, and external parties interested in Universitas Siliwangi-related information. However, the website's utilization lacks evaluation by users and usability testing. Initial observations reveal that only a few students and high school students use this website as a source of Universitas Siliwangi-related information. Therefore, this research aims to examine the usability and usefulness of the website for users and to promote the university. The findings of this study will serve as the basis for university website development and benefit Universitas Siliwangi. The method used to measure the website's usability is the Jakob Nielsen method with user satisfaction survey techniques. The results of this research indicate that the usability of the Universitas Siliwangi website falls into the high category. With users' information needs met on the website, it is expected that they will feel satisfied and inclined to revisit the site. Descriptive analysis shows that students give high ratings to the usability of the Universitas Siliwangi website, although there are still some shortcomings that need to be addressed in certain aspects.